2004
DOI: 10.1038/nature02800
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulatory code of a eukaryotic genome

Abstract: DNA-binding transcriptional regulators interpret the genome's regulatory code by binding to specific sequences to induce or repress gene expression 1 . Comparative genomics has recently been used to identify potential cis-regulatory sequences within the yeast genome on the basis of phylogenetic conservation 2-6 , but this information alone does not reveal if or when transcriptional regulators occupy these binding sites. We have constructed an initial map of yeast's transcriptional regulatory code by identifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

84
2,937
9
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,969 publications
(3,069 citation statements)
references
References 29 publications
84
2,937
9
8
Order By: Relevance
“…The comparison using the ChIP-chip co-binding network [6] shows that, when the recall is less than 0.025, our precision is better (Figure 1b). The advantage for the top predictions indicates that our method is better for species-specific predictions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The comparison using the ChIP-chip co-binding network [6] shows that, when the recall is less than 0.025, our precision is better (Figure 1b). The advantage for the top predictions indicates that our method is better for species-specific predictions.…”
Section: Resultsmentioning
confidence: 99%
“…The first reference network, the annotated regulon network, is constructed by linking pairs of genes belonging to the same annotated regulon that have been proved by low-throughput experiments [41,42]. The second reference network, known as the co-binding network, is derived from high-throughput ChIP-chip data [6], where we link any pair of genes that are shown to be bound by at least one common TF in the ChIP-chip data (with p -value < 0.001). The annotated regulon network is smaller and less complete than the co-binding network, but probably more accurate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TFs were scored by the modulation in expression level of genes that the TFs bind in the upstream region according to ChIP-chip data [24]. Therefore, the score is not indicative of change in the TF expression level itself, but of the genes under its influence.…”
Section: Resultsmentioning
confidence: 99%
“…In eukaryotic cells, TF localization fluctuates, often between cytoplasm and nucleus [7]. Although it has been observed that promoters can pool on the genome in clusters [8] it has not previously been seen that TFs themselves act in clusters, but instead are largely assumed to act as single molecules. Simulations which embody diffusion and binding suggest that multivalent TFs could, in principle, facilitate intersegment transfer [9].…”
Section: Introductionmentioning
confidence: 99%